1989
DOI: 10.1002/bms.1200180902
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of organophosphorus pesticide residues in food applying gas chromatography/mass spectrometry with chemical ionization and pulsed positive negative detection

Abstract: A conñrmatory teshnique for residue analysis of organophosphorus pesticides in food samples applying gas chromatography/mass spectrometry is described. The use of capillary columns is essential to achieve the separation of the great number of pesticides in use. Chemical ionization with the simultaneous recording of positive and negative ions results in the highest detection sensitivity for al1 72 compounds. A selection of three ions was made for each pesticide and the parameters were optimized to gain highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1991
1991
2002
2002

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…In contrast to the PI mode, fragment ions predominated in the NI mass spectra of OPs and their metabolites. Many of the ions for OPs seen in this work have been noted in other studies involving NCI (Stan and Kellner, 1982), pulsed positive negative Cl (Stan and Kellner, 1989), and TSP/LC-MS in the negative mode (Durand et al, 1991). Discussions of the mechanisms for the structure and formation of these ion fragments are found in these references.…”
Section: Methodssupporting
confidence: 61%
“…In contrast to the PI mode, fragment ions predominated in the NI mass spectra of OPs and their metabolites. Many of the ions for OPs seen in this work have been noted in other studies involving NCI (Stan and Kellner, 1982), pulsed positive negative Cl (Stan and Kellner, 1989), and TSP/LC-MS in the negative mode (Durand et al, 1991). Discussions of the mechanisms for the structure and formation of these ion fragments are found in these references.…”
Section: Methodssupporting
confidence: 61%
“…This behaviour differs from most of the organophosphorus pesticides which exhibit [M+NH 4 ] + as base peak (20,21). The higher proton affinity of fenamiphos has also been shown under conventional chemical ionization conditions and shows better sensitivity under positive chemical ionization than negative chemical ionization conditions (22). Under TSP-MS, fenamiphos sulfoxide exhibits a base peak similar to fenamiphos (23) but vamidothion sulfone has [M+NH 4 ] + as base peak, which indicated that the addition of the sulfone group has decreased the proton affinity of the compound below that of ammonia.…”
Section: Photolysis Experimentsmentioning
confidence: 88%
“…The main limitations of this technique lie in the relatively low sensitivity obtained for some pesticide/commodity combinations in fullscan mode and the occurrence of matrix interferences in the samples that can lead to false positive and/or false negative detection. In this sense, the employment of more sensitive and selective alternative modes of operation, such as selected ion monitoring (SIM), 17 chemical ionisation (CI) 18 or tandem mass spectrometry (MS-MS) 19,20 has been shown to be the best choice in terms of performance.…”
Section: Introductionmentioning
confidence: 99%